Roles of Urban Indigenous Community Members in Collaborative Field-Based Teacher Preparation. (November 2016) - Lees, Anna
This qualitative case study explored a community–university partnership for teacher preparation with an urban Indigenous community organization. The study examined the roles of Indigenous community partners as co-teacher educators working to better prepare teachers for the needs of urban Indigenous children and communities. The author collected data through focus groups with Indigenous participants before and after engagement with the partnership, direct observations of partnership activities where Indigenous participants interacted with teacher candidates and university faculty, and offered individual interviews for all participants. Indigenous Postcolonial Theory (IPT) guided this research and offered a lens to examine the perspectives of urban Indigenous community members engaged as co-teacher educators in field-based teacher preparation. This study held implications for continued development of Indigenous community–university partnerships and furthering the role of community leaders in teacher preparation to advance efforts of Indigenous postcolonialism through self-education.